2023
DOI: 10.1093/lambio/ovad100
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of virulence factors, phylogenetic grouping, multiple-locus variable number tandem repeat analysis, and antimicrobial susceptibility of E. coli isolated from aborted bovine fetal tissue

Ediz Kağan Özgen,
Berna Yanmaz,
Perihan Şerifoğlu Bağatir

Abstract: Escherichia coli is an important microorganism for cattle breeding. The aim of this study was to investigate the presence of phylogenetic groups, virulence factors, genotyping with multi-locus variable tandem repeat analysis (MLVA), and susceptibility to commonly used antimicrobial agents in E. coli strains isolated from aborted bovine fetal samples. In this study, phylogrouping and various virulence genes were analyzed by PCR in E. coli strains isolated from 637 bovine fetal tissue samples. Consequently, E. c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Coura et al ( 118 ) found that the phylogroups B1 and E were associated with E. coli isolated from cattle, while phylogroups B2 and D were associated with E. coli collected from water buffalo ( 118 ). Recently, Özgen et al ( 119 ) reported that the phylogenetic group B1 has been observed in the case of bovine abortions ( 119 ). Notably, Aguirre-Sánchez et al ( 120 ) mentioned that the phylogroup B1 for E. coli isolated from cattle located in Mexico demonstrated a significant relationship with food sources ( 120 ).…”
Section: Discussionmentioning
confidence: 99%
“…Coura et al ( 118 ) found that the phylogroups B1 and E were associated with E. coli isolated from cattle, while phylogroups B2 and D were associated with E. coli collected from water buffalo ( 118 ). Recently, Özgen et al ( 119 ) reported that the phylogenetic group B1 has been observed in the case of bovine abortions ( 119 ). Notably, Aguirre-Sánchez et al ( 120 ) mentioned that the phylogroup B1 for E. coli isolated from cattle located in Mexico demonstrated a significant relationship with food sources ( 120 ).…”
Section: Discussionmentioning
confidence: 99%